Синестезия и “предметно-изобрaзительные” способы обознaчения вкусовых ощущений - Лечицкая, Ж. В. (Kalbotyra, 1988)
The article presents a description of the interrelation between adjectives denoting taste and other groups of adjectives denoting sensual perceptions (the phenomenon of synesthesia), as well as the means of using relative adjectives to denote perceptions.